1997
DOI: 10.1074/jbc.272.4.2082
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Factor X Interactive Site in the A1 Subunit of Factor VIIIa

Abstract: The protein cofactor, factor (F) VIIIa, is required for the efficient conversion of the substrate FX to FXa by the serine protease FIXa. The interaction between human FVIII (and its constituent subunits) and FX was characterized using a solid phase binding assay performed in the absence of phospholipid and FIXa. Saturable binding of FX to heterodimeric FVIII, the FVIII heavy chain (contiguous A1-A2 domains), the FVIIIa-derived A1/A3-C1-C2 dimer, and the isolated A1 subunit was observed with estimated Kd values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 41 publications
4
105
1
Order By: Relevance
“…Earlier studies indicated that this acidic region constitutes a low affinity (K d ϳ1-3 M) factor X-interactive site (14). Cross-linking studies using EDC identified a salt bridge(s) between residues 349 -372 of acidic region and the serine protease-forming domain of the factor X heavy chain exclusive of the activation peptide (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies indicated that this acidic region constitutes a low affinity (K d ϳ1-3 M) factor X-interactive site (14). Cross-linking studies using EDC identified a salt bridge(s) between residues 349 -372 of acidic region and the serine protease-forming domain of the factor X heavy chain exclusive of the activation peptide (27).…”
Section: Discussionmentioning
confidence: 99%
“…This region is also implicated in the binding of factor X (14), and recent evidence suggests a functional contribution to the K m for factor X interaction with factor Xase (13). The acidic region is bracketed by Arg 336 and Arg 372 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipid vesicles containing 20% phosphatidylserine (PS), 40% phosphatidylcholine (PC), and 40% phosphatidylethanolamine (PE) were prepared using octyl glucoside as described previously (22). The A1/A3C1C2 dimer was purified by Mono S chromatography following activation of WT factor VIII by thrombin as described (23). The A2 domain-specific monoclonal antibody R8B12 was obtained from Green Mountain Antibodies (Burlington, VT).…”
Section: Methodsmentioning
confidence: 99%
“…The exact mechanism by which FVIIIa enhances the catalytic activity of FIXa toward FX is still unknown. It is generally believed that FVIIIa has three functions within the intrinsic FX-activating complex: (i) FVIIIa stabilizes a conformation of FIXa that has strongly increased protease activity toward FX, (ii) FVIIIa acts as a receptor for FIXa on activated platelets (2), which in vivo provide the procoagulant phospholipid surface (21), and (iii) more recent data indicate that FVIIIa directs the cleavage sites in FX toward the active site of FIXa (22). We identified a murine monoclonal antibody, 224AE3, that specifically binds to human FIXa and that enhances the catalytic activity of the FVIIIa-FIXa-Ca 2ϩ -phospholipid complex.…”
Section: Discussionmentioning
confidence: 99%